2007
DOI: 10.2172/922532
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear System Identification for Damage Detection

Abstract: About the cover: The figure in the upper left is an idealization of an actual test structure with loose internal parts that was subjected to an 18 Hz base input on a shake table. Los Alamos National Laboratory, an affirmative action/ equal opportunity employer, is operated by Los Alamos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 92 publications
0
67
0
Order By: Relevance
“…The coherence function can be utilized to discriminate linear and nonlinear structural systems [14]. This function value ranges from 0.0 to 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…The coherence function can be utilized to discriminate linear and nonlinear structural systems [14]. This function value ranges from 0.0 to 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…Modeling hysteresis (e.g., [4,15,29,39,40,46]) is inherently challenging; however, it is necessary in that it has broad utility in many engineering disciplines, including smart structures, robotics, mechatronics, structural control, structural health monitoring, damage detection, and earthquake engineering. Rapid advances in sensor technology are providing researchers in different fields of science and engineering with valuable data collected from real-world measurements.…”
Section: Motivations Of This Studymentioning
confidence: 99%
“…However they are suitable for rotating machinery and structural integrity assessment respectively. SHM combines both damage detection philosophies and translates them into an active/passive of online/offline systems in order to monitor the health status of the structure (Farrar et al, 2007) as shown in Fig. 3.…”
Section: Structural Health Monitoring (Shm)mentioning
confidence: 99%